When does advice impact startup performance?. (8th February 2019) - Chatterji, Aaron; Delecourt, Solène; Hasan, Sharique; Koning, Rembrand
Abstract : Why do some entrepreneurs thrive while others fail? We explore whether the advice entrepreneurs receive about managing their employees influences their startup's performance. We conducted a randomized field experiment in India with 100 high‐growth technology firms whose founders received in‐person advice from other entrepreneurs who varied in their managerial style. We find that entrepreneurs who received advice from peers with a formal approach to managing people—instituting regular meetings, setting goals consistently, and providing frequent feedback to employees—grew 28% larger and were 10 percentage points less likely to fail than those who got advice from peers with an informal approach to managing people, 2 years after our intervention. Entrepreneurs with MBAs or accelerator experience did not respond to this intervention, suggesting that formal training can limit the spread of peer advice.